1992
DOI: 10.1016/0378-1097(92)90627-z
|View full text |Cite
|
Sign up to set email alerts
|

Intraspecific hybridisation of Trichoderma pseudokoningii by anastomosis and by protoplast fusion

Abstract: Double auxotrophic and morphological mutants of Trichoderma pseudokoningii Rifai were fused by anastomosis and by protoplast fusion. The recovery of recombinants from heterokaryons on different selective media and from heterokaryotic colonies indicated the occurrence of parasexual events. Prototrophic colonies growing on minimal medium produced binucleate spores, green in colour, revealing a non-autonomous system for conidial pigmentation. Recombinants were obtained from these dikaryotic colonies suggesting th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
4

Year Published

1995
1995
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 17 publications
(6 reference statements)
0
8
0
4
Order By: Relevance
“…Unstable recombinants, which changed preferentially to one of the parental types, were also detected. In all original colonies analyzed, except one, parental types always were detected besides the recombinants, indicating a strong heterokaryotic condition in this organism, which produces uninucleate and also a lower frequency of 0.1% of binucleate conidia (Furlaneto and Pizzirani-Kleiner 1992). This situation makes it difficult to estimate recombinant occurrence frequencies, unless strains with good genetic markers are used and careful single spore colony recovery of possible recombinants is performed.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Unstable recombinants, which changed preferentially to one of the parental types, were also detected. In all original colonies analyzed, except one, parental types always were detected besides the recombinants, indicating a strong heterokaryotic condition in this organism, which produces uninucleate and also a lower frequency of 0.1% of binucleate conidia (Furlaneto and Pizzirani-Kleiner 1992). This situation makes it difficult to estimate recombinant occurrence frequencies, unless strains with good genetic markers are used and careful single spore colony recovery of possible recombinants is performed.…”
mentioning
confidence: 98%
“…Heterokaryons were carried out between two previously obtained strains (Furlaneto and Pizzirani-Kleiner 1992), carrying morphologic and auxotrophic complementary genetic markers (whi4 leu1 thsl + ylo5 rib1 arg2), using liquid minimal medium (MM) with 2% complete medium (CM) and then cultivated on solid MM (Roper 1952), at 28°C. Conidial suspensions from ab + cd heterokaryons (symbolized here by the auxotrophic markers ), which assumed a green wild-type color, were plated onto CM (10'-lo2 conidia/plate) to estimate the total number of viable conidia and the parental ratio.…”
mentioning
confidence: 99%
“…Stasz et al (50) described the occurrence of multinucleated conidia in strains of Trichoderma harzianum and Furlaneto & Pizzirani-Kleiner (23) observed that recombinant prototroph strains of T. pseudokoningii , obtained from crosses via protoplast fusion had binucleated conidia.…”
Section: Resultsmentioning
confidence: 99%
“…Whithin the Trichoderma genus there are descriptions of obtention of recombinants directly from the heterokaryon between strains of several species, which were formed by means of hyphal anastomosis, protoplast fusion or nuclear transfers (3, 7, 23, 37, 38, 46, 47, 48, 49, 50). In several experiments with Trichoderma , the occurrence of characteristic patterns has been observed and would be related to some level of vegetative incompatibility or due to limited vegetative compatibility (5, 46, 48, 49).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation